Implementasi Pembayaran Pajak Kendaraan Bermotor di Kabupaten Karangasem - Lukman Hakimi; Ida Ayu Putu Widiati; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2021)
The main component of implementing regional autonomy is the activity of exploring more of the potential that exists in the region, especially taxes. The Revenue Service Unit (UPT) of Karangasem Regency is required to strive for achieving targets and increasing income in a sustainable manner to support the increase in Regional Original Income. The purposes of this study are to analyze the implementation of motor vehicle tax collection at SAMSAT Karangasem district and the supporting and inhibitor factors in the implementation of motor vehicle tax payments at Samsat Karangasem district. The research method used is an empirical legal research method with a statutory, a conceptual and a sociological approach. The technique of collecting legal materials is done by field observation through interviews. The sources of legal materials used are primary legal materials and secondary legal materials. Data analysis in this study used a qualitative descriptive analysis method. The results of the study indicate that the Bali Provincial Retribution in Karangasem Regency starts from the registration, determination and payment stage based on the Bali Provincial Regulation No. 1 of 2011 concerning Regional Regulations (PERDA) on Regional Taxes. Supporting factors, namely adequate human resources, administrative processes with a computerized system, the existence of mobile SAMSAT. Inhibiting Factors in the Implementation of Motor Vehicle Tax Payments at SAMSAT Karangasem Regency, namely the lack of awareness of taxpayers, incomplete taxpayer data, transfer of motorized vehicles without being renamed, owners changing places of residence.